2020
DOI: 10.1002/hbm.25290
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the role of amygdala and insula in an attentional capture by emotional stimuli task

Abstract: Our senses are constantly monitoring the environment for emotionally salient stimuli that are potentially relevant for survival. Because of our limited cognitive resources, emotionally salient distractors prolong reaction times (RTs) as compared to neutral distractors. In addition, many studies have reported fMRI blood oxygen level‐dependent (BOLD) activation of both the amygdala and the anterior insula for similar valence contrasts. However, a direct correlation of trail‐by‐trial BOLD activity with RTs has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Our results suggest that the latter provides directed influences to the former when error-monitoring is increased. Our previous study and other recent publications showed that insula activity is correlated to behavioral performance and reaction times in distinct tasks (Castelhano et al, 2019;Marxen et al, 2021). Evidence that the insular cortex also seems to be involved in performance monitoring (Bastin et al, 2017;Billeke et al, 2020) and our Granger causality findings showing that error-monitoring-related activity triggers a shift of causal influences to frontal regions, in particular, ACC, make a strong basis toward the notion that the insula is a pivotal region during error-monitoring.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results suggest that the latter provides directed influences to the former when error-monitoring is increased. Our previous study and other recent publications showed that insula activity is correlated to behavioral performance and reaction times in distinct tasks (Castelhano et al, 2019;Marxen et al, 2021). Evidence that the insular cortex also seems to be involved in performance monitoring (Bastin et al, 2017;Billeke et al, 2020) and our Granger causality findings showing that error-monitoring-related activity triggers a shift of causal influences to frontal regions, in particular, ACC, make a strong basis toward the notion that the insula is a pivotal region during error-monitoring.…”
Section: Discussionsupporting
confidence: 78%
“…Parts of the insula have been reported as being associated with emotional processing, memory, decision, and sensory regulation in relation to autonomic control ( Marxen et al, 2021 ). This region is an important part of the salience network, which not only drives attention toward target stimuli but also relates to decision-making and error-monitoring ( Droutman et al, 2015 ; Lamichhane et al, 2016 ; Bastin et al, 2017 ; Billeke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies might test reliability within short time intervals in adults first before applying paradigms to developing age groups in longitudinal designs ( Herting et al, 2018 ). An overall limitation of the current task is that matching abstract stimuli did not induce the expected attention capture effect, therefore our group developed an alternative task ( Marxen et al, 2021 ). The unexpected findings, especially of the late increase in amygdala activation might be driven by participants > 20 years that contain fewer data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Functional impairments in everyday life or even mental disorders, such as depression, may arise when this process is not well‐balanced (Pilhatsch et al, 2014 ). In our task, participants are presented with a left‐ or right‐pointing triangle, preceded and followed by a very brief display of a distractor image (Figure 1 and [Marxen et al, 2021 ]). Subjects have to indicate as quickly as possible the pointing direction of the triangle by a button press and will respond slower, in average, when the distractor image is perceived as negative in valence (threatening, disgusting, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…as compared to neutral (Gupta et al, 2016 ; Padmala et al, 2017 ). This response slowing is thought to reflect a withdrawal of limited cognitive resources from executing the task towards evaluating the potential threat (Marxen et al, 2021 ; Schmidt et al, 2015 ). fMRI studies show a well‐known, extended network of brain regions that react stronger to negative emotional images as compared to neutral images (Figure 2 and [Dolcos et al, 2011 ; Marxen et al, 2021 ]).…”
Section: Introductionmentioning
confidence: 99%